Evaluating kinetic light-shelves and their impacts on daylighting performance - Ali A. S. Bahdad; S F Syed Fadzil; N Taib (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
This study aims to evaluate the natural illumination levels obtained using Light-Shelves Techniques (LST) under real tropical conditions in Malaysia. Two parameters of manually controllable of LST design have been examined; Location (L) and Position (P) which were placed on the south-façade window. A scaled-model experiment was applied to determine the illumination levels achieved by LST under real sky conditions. Computer simulation results using Radiance engine were used to validate the scaled-model method used indicators Daylight Ratio (DR%), and it observed to be in great concurrence with physical scaled-model data obtained under tropic sky which is mostly an intermediate sky. The maximum average level percentage of DR% differences between scaled-model and simulation was 1.8% (≤10%). The results showed the performance of the LST can be improved by controlling the location and position. The most optimal LST for south-facing orientation was found in different times at locations in the external L1 and L2 at P1 give the best illuminance near the window and the back. The best improvement in daylighting at deep office area (SP3) were 4.2% at 9:00h on Jan, 4.7% and 7.3% at 12:00h, and by 27% and 2.1% at 15:00h on Jan and March respectively.